Herbal Medicines as Adjunctive Therapy for Oral Squamous Cell Carcinoma Management: a Case Report: Obat Herbal sebagai Terapi Tambahan untuk Manajemen Karsinoma Sel Skuamosa Oral: Laporan Kasus - Ani Megawati; Riani Setiadhi (Dentika: Dental Journal, 2022)
Oral Squamous Cell Carcinoma (OSCC) is the most frequent oral cancer. The management for OSCC are surgery, chemotherapy, and radiotherapy. Chemotherapy and radiotherapy have high toxicity and side effects, therefore effort are needed to reduce them. Several studies show that herbal medicines have anticancer effects with lower toxicity and side effects. The objective is to discuss about management of OSCC using chemotherapy and anticancer herbal medicines as adjunctive therapy.Â  A 59-year-old man came to the oral medicine clinic complaining a painful ulcer on the right tongue since 8 months ago. The ulcer had been enlarged in the last 3 months and the tongue was difficult to be moved. He used pain relievers and aloe vera gel but there was no improvement. He smoked one pack a day since 40 years ago. Intraoral showed an irregular indurated endophytic mass with an ulcer on the right lateral of the tongue. An incisional biopsy was performed and the histopathological diagnosis was poorly differentiated OSCC. The patient was referred to the oncology department and advised for chemotherapy 6 cycles per 3 weeks. He also used herbal medicines containing Panax ginseng radix, Panax pseudoginseng radix, Ophiopogonis japonicus, Ganoderma lucidum, Ligusticum wallichii rhizoma, and Atractylodes macrocephala rhizoma. The content of these herbal medicines have anticancer and immunomodulatory effects. After the second cycle of chemotherapy, there was a significant improvement. OSCC management with chemotherapy combined with anticancer herbal medicines can increase the success of therapy and reduce the side effects of chemotherapy.